Dinamika Kebebasan Ekonomi dan Faktor Ekonomi: Pengaruhnya pada Pertumbuhan di 30 Negara (2013–2022) - Muhammad Sofyan Farishi; Wiwin Priana Primandhana; Wirya Wardaya (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the influence of economic freedom and macroeconomic factors on economic growth in 30 countries during the period 2013-2022. In this context, Economic Freedom (EC) is measured using the economic freedom index which includes aspects such as trade freedom, regulation, and fiscal policy. Meanwhile, the macroeconomic factors studied include Inflation (INF), International Trade (PI), Foreign Direct Investment (FDI) and Population Growth (POP). The data used in this study are secondary, obtained from international sources such as the World Bank and the Heritage Foundation's Index of Economic Freedom. The analytical method applied is panel data regression to test the relationship between these variables and economic growth as the dependent variable. The results of the study show that economic freedom significantly affects economic growth, where countries with higher levels of economic freedom tend to have better economic growth. In addition, macroeconomic factors such as International Trade, FDI and Population Growth were also found to have a positive impact on economic growth, while Inflation has a negative impact because every country wants a low inflation rate. This research makes an important contribution to the understanding of the factors that influence economic growth, as well as the application of economic policies that can be implemented by countries with varying levels of economic freedom